Determinants of peri-urban and urban agricultural locational choicebehaviour in Lagos, Nigeria (2014)
This article quantitatively assessed factors that shape locational choice behaviour of urban farmers. Three hundred questionnaires were randomly administered to farmers in ten localities with a view to identifying factors that shape their locational choice behaviour. The average number of farmers per locality was designated as the index of attractiveness and was correlated with six broad categories of factors identified by farmers as influential in urban agricultural site selection. These broad factors are proximity to water, proximity to residence, access to land, proximity to market, suitable fertile soils, and availability of labour. These factors were subsequently broken down to sixteen categories. Almost all the variables exhibited negatively significant correlations with the index of attractiveness. Urban farmers prefer sites which were closer to water, free with minimal lease and rental cost, and also sites with fertile soil that is closer to farmer’s residence, where aggregate costs of production is minimal and labour relatively avail-able. The results obtained can be used in mainstreaming urban agriculture into city planning while at the same time provide avenue for increased urban agricultural productivity.